Application of Android Game-Based Learning to Overcome Smoking Emergencies in Adolescents - Joko Tri Wahyudi; M Umar Ardan Al Hakim (Jurnal Inspirasi Kesehatan, 2023)
Background: Teenagers tend to have a desire to know big. Studies show that students are more Possible To smoke than adults. Especially based on the results research latest says that smoking among teenagers every year the more increase. In general, they confess Already start smoking between 9 to 12 years old, Teenagers tend to have a desire to know big. Studies show that students are more Possible To smoke than adults, factors that have a very large impact on the emergence of various diseases. A smoker has a 2 to 4 times risk of developing coronary heart disease and a higher risk of developing lung cancer. Especially based on the results research latest says that smoking among teenagers every year the more increase. Purpose: To apply learning android games free as a try to overcome emergency smoking in adolescents. Method: This activity is Community Service that applies an Android game-based learning method to overcome smoking emergencies in Indonesian teenagers. The target of community service is 30 grade 11 vocational students. To measure motivation to stop smoking, the writer uses a questionnaire Richmond-Test. Results: Based on the results obtained mean pre-test value is 5.27 meanwhile mark the post-test mean is 8.27. Conclusion: The learning method is based on Android games that can increase the Spirit of teenagers To stop smoking.